Spotlight [videorecording (DVD)] - McCarthy, Tom, 1966-; Ruffalo, Mark; Keaton, Michael, 1951-; McAdams, Rachel, 1978-; Schreiber, Liev; Tucci, Stanley; Crudup, Billy, 1968-; Guilfoyle, Paul; Sheridan, Jamey; Cariou, Len (Universal Studios Home Entertainment, 2016)
The riveting true story of the Pulitzer Prize-winning Boston Globe investigation that would rock the city and cause a crisis in one of the world's oldest and most trusted institutions. When the newspaper's tenacious 'Spotlight' team of reporters delve into allegations of abuse in the Catholic Church, their year-long investigation uncovers a decades-long cover-up at the highest levels of Boston's religious, legal, and government establishment.